2003
DOI: 10.1074/jbc.m304363200
|View full text |Cite
|
Sign up to set email alerts
|

Raloxifene Inhibits Estrogen-induced Up-regulation of Telomerase Activity in a Human Breast Cancer Cell Line

Abstract: The mechanism by which raloxifene acts in the chemoprevention of breast cancer remains unclear. Because telomerase activity is involved in estrogen-induced carcinogenesis, we examined the effect of raloxifene on estrogen-induced up-regulation of telomerase activity in MCF-7 human breast cancer cell line. Raloxifene inhibited the induction of cell growth and telomerase activity by 17␤-estradiol (E2). Raloxifene inhibited the E2-induced expression of the human telomerase catalytic subunit (hTERT), and transient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 46 publications
3
43
0
Order By: Relevance
“…hTERT-expressing cells were evaluated for cytoplasmic (C), nuclear-cytoplasmic (N þ C), and nuclear (N) fluorescence (Figure 9a). E 2 induced nuclear accumulation of hTERT from 30 min to 24 h in Caov-3 cells (Figure 9b), as we have also demonstrated in MCF-7 cells (Kawagoe et al, 2003). Most of the TERT protein was also localized in the cytoplasm under normal serum conditions (data not shown).…”
Section: E 2 Induces Nuclear Accumulation Of Htertsupporting
confidence: 63%
See 1 more Smart Citation
“…hTERT-expressing cells were evaluated for cytoplasmic (C), nuclear-cytoplasmic (N þ C), and nuclear (N) fluorescence (Figure 9a). E 2 induced nuclear accumulation of hTERT from 30 min to 24 h in Caov-3 cells (Figure 9b), as we have also demonstrated in MCF-7 cells (Kawagoe et al, 2003). Most of the TERT protein was also localized in the cytoplasm under normal serum conditions (data not shown).…”
Section: E 2 Induces Nuclear Accumulation Of Htertsupporting
confidence: 63%
“…Most of the TERT protein was also localized in the cytoplasm under normal serum conditions (data not shown). Pretreatment with LY294002, ICI 182,780, or BAY11-7082 attenuated the E 2 -induced nuclear accumulation of hTERT in both Caov-3 (Figure 9c, left panel) and MCF-7 (Figure 9c, right panel) (Kawagoe et al, 2003) cells. These data suggest that E 2 -induced nuclear accumulation of hTERT is mediated by ER via a PI3K/Akt/NFkB cascade in both Caov-3 and MCF-7 cells.…”
Section: E 2 Induces Nuclear Accumulation Of Htertmentioning
confidence: 99%
“…Further investigation indicates that NF-kB is necessary for human Tlymphotropic virus type 1 (HTLV-1) oncoprotein Tax induced telomerase expression during transmission of HTLV-1 to primary T cells (Sinha-Datta et al, 2004). In addition, NF-kB is reported to mediate estrogeninduced telomerase expression in MCF-7 human breast cancer cells (Kawagoe et al, 2003). These reports suggest that both c-IAP2 and telomerase promoters might be controlled by NF-kB.…”
Section: Discussionmentioning
confidence: 97%
“…In this sense, our results suggest that PZsc may have a stronger ability to promote PCa progression. Several groups have reported that sex hormones can regulate hTERT expression, [54][55][56] but the mechanism is unknown. We also found that E2 increased hTERT mRNA expression.…”
Section: Differential Effects Of Pzsc and Tzsc On Pc3 Cellsmentioning
confidence: 99%